2009
DOI: 10.1161/circheartfailure.108.845487
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Exercise Training Improves Survival and Ventricular Remodeling in an Animal Model of Left Ventricular Volume Overload

Abstract: Background: Exercise training has beneficial effects in patients with heart failure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 37 publications
5
49
0
Order By: Relevance
“…To our surprise, left ventricular function in hLPL0 mice did not worsen after 6 wk of swim training but actually improved. Our studies with a model of heart failure due specifically to a genetic loss of lipid uptake by the heart are consistent with other studies in both animal models of heart failure (11,32) and heart failure patients that found exercise-induced improvements in cardiac ejection fraction (18,24,55).…”
Section: Discussionsupporting
confidence: 91%
“…To our surprise, left ventricular function in hLPL0 mice did not worsen after 6 wk of swim training but actually improved. Our studies with a model of heart failure due specifically to a genetic loss of lipid uptake by the heart are consistent with other studies in both animal models of heart failure (11,32) and heart failure patients that found exercise-induced improvements in cardiac ejection fraction (18,24,55).…”
Section: Discussionsupporting
confidence: 91%
“…Although interstitial fibrosis is not an early feature of this animal model of eccentric LV remodeling, significant accumulation of collagen is present in later stages (≥6 months). 16,22 Our results suggest that the dilated hearts of Cpt-treated AR animals tolerated the abnormal hemodynamic overload and maintained a near normal myocardial metabolic profile. We previously showed that blood pressure in AR animals treated with Cpt is only slightly reduced and had similar findings in this protocol.…”
Section: Discussionmentioning
confidence: 65%
“…Our findings also confirm our previous observations of the benefits of Cpt in AR. 5,22 The controversy regarding the efficacy of vasodilators, including ACEI in the treatment of AR, is far from resolved. Recently, a meta-analysis of all the randomized clinical trials that evaluated vasodilators in AR 23 showed that the evidence points toward the efficacy of vasodilators although a wide discrepancy exists between the trials' design and results.…”
Section: Discussionmentioning
confidence: 99%
“…Groban et al (Groban et al 2008) performed a 4-week treadmill running program with 6 and 28 months old Fischer 344 × Brown Norway rats resulting in improved mitral annular descent (e′) with older rats similar to the young adult rats without improvements in filling pressures, or E/e′ ratios. Lachance, et al (Lachance et al 2009) required adult rats to train at a moderate intensity for 9 months or remain sedentary and observed significant improvements in LV diastolic parameters as early as 3 months into the study period. In addition to improved LV filling characteristics, these authors noted a reduction in myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%